Lesbian herstory archives subject files . - Nestle, Joan, 1940- (Primary Source Microfilm, 2004)
Contains information on every conceivable aspect of lesbian life and concerns, from abortion to African-American lesbians, lesbian mothers, gay civil rights, women's liberation movement, domestic partnership, older lesbians, and Native American lesbians, to name just a few of the important subjects. The materials consist of clippings, flyers, brochures, conference materials, reports, correspondence, and other printed ephemera. A strength of the collection is its vast scope and national coverage.